Pusat penataran ilmu dan bahasa:pengalaman dan cabaran - Totu, Andreas (Universiti Kebangsaan Malaysia, 2010)
This manuscript explains the experiences and challenges faced by the Centre for the Promotion of Knowledge and Language Learning (commonly known as PPIB) as the main entity to promote general studies in the Universiti Malaysia Sabah. The General Studies concept has long been incorporated into the Malaysian system of education particularly in the institutes of higher learning. Nevertheless, its importance and benefits have yet to be understood by various stakeholders of eduction such as the students, parents, societies and to some extent among faculty members. The deficiency in understanding the concept and its advantages led to the lack of appreciation, henceforth contributes to the ineffectiveness in terms of implementation and outcomes. The needs to inculcate a positive attitude towards general studies among stakeholders are paramount in order to produce a balanced graduate that possesses both knowledge and soft skills. The PPIB has initiated several measures to address the deficiency, however wider and concerted efforts on the national level are required to ensure the country will have first class human capitals in the future.